2012
DOI: 10.1308/003588412x13171221592014
|View full text |Cite
|
Sign up to set email alerts
|

Have the media influenced the use of hip resurfacing arthroplasty? A review of UK print media

Abstract: INTRODUCTIONThe aim of this study was to look at the different claims made about hip resurfacing arthroplasty in the popular UK print media and how this relates to findings in the scientific literature.METHODSA review of UK popular print media from January 1992 to June 2011 was performed using the Lexis® Library online news database. Only articles discussing the clinical results of hip resurfacing arthroplasty were included. After excluding duplicates, 49 newspaper articles were found suitable for this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Some patients perceive that there is an unmet demand for hip resurfacing in Canada, which raises important practical questions that extend beyond the scope of this analysis, such as: Is there a need for patient education around this procedure and its long term-effectiveness to enable a greater understanding of why it has limited availability in Canada (see Malviya et al, 2012;Sehatzadeh et al, 2012 for discussions that question the long-term effectiveness of the procedure)? Alternatively, what reforms, if any, are needed to the domestic health care system in order to ensure that such demand is better met?…”
Section: Discussionmentioning
confidence: 99%
“…Some patients perceive that there is an unmet demand for hip resurfacing in Canada, which raises important practical questions that extend beyond the scope of this analysis, such as: Is there a need for patient education around this procedure and its long term-effectiveness to enable a greater understanding of why it has limited availability in Canada (see Malviya et al, 2012;Sehatzadeh et al, 2012 for discussions that question the long-term effectiveness of the procedure)? Alternatively, what reforms, if any, are needed to the domestic health care system in order to ensure that such demand is better met?…”
Section: Discussionmentioning
confidence: 99%
“…Equally concerning are the numerous empirical examples of the misrepresentation of health issues by print media. For example, newspaper articles have been found to be overly positive in the reporting of new surgical interventions, to under-report epidemiological data in relation to the human papillomavirus vaccine25 26 and to report stories about rare diseases more frequently than common conditions 27. Media analyses in the UK have also suggested that negative newspaper portrayals of GPs, and GP pay, are linked to decreasing professional morale and GP recruitment difficulties 28 29.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The available literature is still inconsistent regarding rates of revision, incidences of complications, functional outcomes, patient satisfaction, and long-term results. 4,5 Despite numerous theoretical advantages over THR, HR has been associated with specific complications, for example, periprosthetic femoral neck fractures and metal particle issues, which has therefore caused surgeons confusion in regard to using it as the standard treatment method for younger patients. 6 2 Given that many believe that THR is suitable for the older age group whilst HR is better for the younger age group, the research question is whether age is a factor affecting revision and complication rates.…”
Section: Introductionmentioning
confidence: 99%